Association between early childhood caries and clinical, microbiological, oral hygiene and dietary variables in rural Turkish children - Olmez, Seval; Uzamiş, Meryem; Erdem, Gamze (The Turkish Journal of Pediatrics, 2003)
Mutans streptococci are the principal bacteria isolated from children with early childhood caries (ECC). The aim of this study, therefore, was to determine the relationships between factors related to ECC with salivary mutans streptococci (MS). A total of 95 children with ECC from low-income families in rural Ankara participated in this study. Breast and/or bottle-feeding habits continued in 31.5% of the children beyond 37 months. Forty percent of the bottle-fed, 35.5% of the breast-fed, and 29.4% of the breast-and bottle-fed children continued their habits beyond 37 months. Caries prevalence was significantly related to the age and feeding habits. Eighty one percent of the children did not have a toothbrushing habit and 41% had been taking sweetened medicine. High counts of MS are determined with increasing age, bottle usage, and snacking habits. We concluded that factors related to ECC are common among Turkish children.